Adoption of African indigenous vegetables into agro-pastoral livelihoods for income and food security: Evidence from Kenya. Issue 2 (14th November 2016) - Mshenga, Patience Mlongo; Saidi, Mwanarusi; Nkurumwa, Agnes O.; Magogo, Juma Riziki; Oradu, Shem Ipomai
Abstract : Purpose: The purpose of this paper is to determine the factors influencing adoption of African indigenous vegetables (AIVs) into the agro-pastoral farming systems aiming at improving livelihoods. Design/methodology/approach: The paper is based upon the diffusion theory which is linked to the random utility theory. A survey of 205 agro-pastoral households obtained through multistage sampling technique was used. Factors influencing adoption of AIVs were estimated using a logit model. Findings: Findings indicate that the acreage under AIVs was still very low compared to other crop enterprises with the most common types of AIVs grown being Solanum nigrum, Amaranthus spp ., Cucurbita maxima, Vigna unguiculata, Basella alba and Cleome gynandra . Factors influencing adoption were found to be gender, age, farm size, education level, off-farm income and number of visits to extension officer. Research limitations/implications: Limitations include reliance on respondents' willingness to provide correct information. Originality/value: This paper adds value in its contribution to literature on diversifying agro-pastoral livelihoods through production of AIVs for income and food security.